Combined transcriptome and metabolome analyses reveal the effects of selenium on the growth and quality of Lilium lancifolium - Jiang, Xiaogang; Zhou, Wuxian; Li, Darong; Wang, Hua; Yang, Yuying; You, Jinwen; Liu, Haihua; Ai, Lunqiang; Zhang, Meide (Frontiers in Plant Science, 2024)
Lilium lancifolium Thunb (L. lancifolium) is an important medicinal and edible plant with outstanding functionality for selenium (Se) biofortification. However, the molecular response of L. lancifolium to exogenous Se has not been fully elucidated. This study explored the effects of different levels (0, 0.5, 1.0, 2.0, 4.0, and 8.0 mmol/L) of Se on L. lancifolium growth and quality.The results showed that the total Se and organic Se content in L. lancifolium bulbs increased with increasing Se dosage (0-8.0 mmol/L). Moreover, Se stimulated the growth of L. lancifolium at low level (2.0 mmol/L) but showed an inhibitory effect at high levels (≥4.0 mmol/L). Metabolomic and biochemical analyses revealed that the bulb weight and the content of amino acid, soluble sugar, and soluble protein were significantly increased in the 2.0 mmol/L Se treatment compared with those in the control (0 mmol/L Se). Transcriptome and metabolome analyses revealed that the significant upregulation of the GPD1, GPAT and ADPRM genes promoted glycerophospholipid accumulation. Additionally, the significantly upregulated glyA and downregulated asnB, nadB, thrA and SAT genes coordinate to the regulation of amino acid biosynthesis. The significantly upregulated SUS, bgl B, BAM, and SGA1 genes were involved in soluble sugar accumulation under Se treatment.In summary, this study identified the optimal Se concentration (2.0 mmol/L), which significantly improved the growth and nutritional quality of L. lancifolium and contributed to understanding the combined effects of Se treatment on the expression of genes and the accumulation of metabolites in L. lancifolium bulbs.